Face, facial recognition technology and personal privacy - Li, Wei; Hua, Menglian; Sun, Ying; Li, Husheng; Lin, Yanhu (Acta Bioethica, 2023)
The privacy problem of facial recognition technology is that commercial companies obtain people’s facial information without the consent of individuals and use facial information to infringe on the privacy of individuals. The importance of human privacy in facial recognition technology is reflected through facial ethics, which requires others to perform corresponding obligations to individuals, such as oral care. Through the analysis of the privacy issues of facial recognition technology, it is found that the two elements of “without personal informed” and “without personal consent” together form the basis for commercial companies to violate personal privacy. The principle of informed consent includes the principle of informed and the principle of consent, which is derived from the principle of informed consent in medical ethics. This paper improves the principles of informed consent in medicine and ethics to better address facial recognition privacy issues.